Kinetic analysis of start motion on starting block in competitive swimming - Sakai, S.; Koike, S.; Takeda, T.; Takagi, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate kinetic features of start motion with use of an instrumented starting block. This is the first study that quantified joint torques of the whole body during start motion. Six male swimmers dived from the instrumented starting block, which contains force plates and sensors. Four high-speed cameras were used to obtain kinematics data of the swimmers. Inverse dynamics calculation was carried out with use of the kinetics and kinematics data. The results showed that 1) the large pulling up forces exerted by both hands were generated by extension toques of the shoulder joints, 2) the rear side lower limb joints exerted large extension torque to obtain horizontal reaction force, and 3) the knee joint of the front side lower limb exerted large flexion torque to maintain the large vertical reaction force until 60% normalized start motion time.